Women’s sequential and cyclic careers: implications for the career theory - Cybal‐Michalska, Agnieszka (Wydawnictwo Naukowe UAM, 2014)
The article takes up discourse on the development of the career theory that demands taking into account multicontextual changes in the world of work that pose new challenges for women. The subjective shading of the career phenomenon that treats career as an individual’s „property” was clearly stressed. When analysing individual paths of career development for both women and men it is necessary to take its wide scope of conditions into account, as well as inquire into semantic meanings assigned to the reality by the subject in order to interpret and understand past and new experiences. The focus on professional behaviours among women led to considerations on the change of the career concept in its general sense and meaning. Literature on the subject consistently underlines that career patterns will be less and less of a linear character, and more frequently of a sequential and cyclical one. The increase in the role assigned to career forces one to approach it within the category of professional identity development, planning and management skills, and the ability of monitoring one’s career in a lifelong perspective.
Keywords: career; career theory; career development; women’s careers; sequential career; cyclical career; professional identity